Role of Extracorporeal Membrane Oxygenation in Adults and Children With Refractory Septic Shock: A Systematic Review and Meta-Analysis - Yang, Yufan; Xiao, Zhenghui; Huang, Jiaotian; Gong, Ling; Lu, Xiulan (Frontiers in Pediatrics, 2022)
Background The benefits of extracorporeal membrane oxygenation in patients with refractory septic shock remain controversial. Current guidelines on the management of refractory septic shock recommend the consideration of extracorporeal membrane oxygenation as a salvage therapy. The difference between adults and children with septic refractory shock treated with extracorporeal membrane oxygenation has not been previously analyzed. We aimed to review peer-reviewed publications on the role of extracorporeal membrane oxygenation in adults and children with refractory septic shock. Methods Studies reporting on mortality in both adults and children with refractory septic shock supported with extracorporeal membrane oxygenation published in PubMed, Cochrane Library, and Embase databases were included in the meta-analysis. Study eligibility was independently assessed by two authors, and disagreements were resolved by a third author. The outcome measure was survival at discharge. Subgroup analysis included the adult and pediatric groups. Results Of the 293 articles screened, 14 original articles were identified for systematic review and meta-analysis. The cumulative estimate of survival (14 studies, 535 patients) in the cohort was 39% (95% confidence interval [CI]: 27–51%). During the subgroup analysis, the cumulative estimate of survival at discharge in the adult group (6 studies, 276 patients) in the cohort was 18% (95% CI: 10–27%), and that in the pediatric group (8 studies, 259 patients) was 53% (95% CI: 47–59%). Conclusions The survival rate of adults with refractory septic shock requiring extracorporeal membrane oxygenation was 18%, and children with refractory septic shock requiring extracorporeal membrane oxygenation had a higher survival rate (53%) than adults.